Effects of dietary glucose oxidase on growth performance and intestinal health of AA broilers challenged by Clostridium perfringens - Yizhu Zhao (Elsevier, 2022)
ABSTRACT: Arbor Acre (AA) broilers were used as the research object to investigate whether glucose oxidase (GOD) has preventive and relieving effects on necrotic enteritis. The experiment was designed as a factorial arrangement of 2 dietary treatments × 2 infection states. Chickens were fed a basal diet or a diet with 150 U/kg GOD, and were challenged with Clostridium perfringens (Cp) or sterile culture medium. In our study, Cp challenge led to intestinal injury, as evidenced by reducing the average daily gain and the average daily feed intake of AA broilers of 14 to 21 d (P < 0.05), increasing the intestinal jejunal lesion score (P < 0.05), reducing the jejunal villi height and villi height/crypt depth (P < 0.05), upregulating the mRNA expression levels jejunal IFN-γ (P < 0.05). The dietary GOD had no significant effects on the growth performance of each growth period, but significantly decreased the ileal pH, increased the height of villi and the ratio of villi height to crypt depth (P < 0.05) and the expression levels of Occludin and Zonula occludens-1 (ZO-1) at d 21. Moreover, dietary GOD and the Cp challenge significantly altered the composition of 21-d ileal microbiota. The Cp challenge decreased the relative abundance of genus Lactobacillus (P = 0.057), and increased the relative abundance of genus Romboutsia (P < 0.05) and genus Veillonella (P = 0.088). The dietary GOD tended to increase the relative abundance of genus Helicobacter (P = 0.066) and decrease the relative abundance of genus Streptococcus (P = 0.071). This study has shown that the supplementation of GOD could promote the integrity of intestinal barrier and the balance of ileal microbiota, but the effects of GOD on NE broilers and its application in actual production need to be further confirmed.